Effects of heat stress, dietary energy density and exogenous porcine somatotropin on tile growth performance of finishing pigs - Stoner, G.R.; Nichols, David A.; Allee, G.L.; Schricker, B.R.; Nelssen, Jim L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
This experiment was conducted to determine the interactive effects of environmental temperature porcine somatotropin (pST) and dietary energy density on the growth performance of finishing pigs. Forty-eight barrows were allotted randomly to four environmental chambers (EC) in a split plot design with two EClwhole plot (WP). Each EC (12 barrows/EC) represented one subplot (SP). The WP 24-h environmental cycles were: thermal neutral (TN), 8 h at 75°F and 50% relative humidity (RH)-1 h transition-14 h at 68°F and 60% RH-1 h transition; and heat stress (HS), 8 h at 95°F and 60% RH-1 h transition-14 h at 82°F and 80% RH-1 h transition. Each SP was a 2 x 3 factorial with two treatments (pigs were injected daily with either 4 mg pST (+) or placebo (-)) and three dietary energy densities (lA8, 1.60, and 1.71 Mcal ME/lb). Diets were formulated to contain 19.2% crude protein and at least 200% of NRC (1988) recommendations for essential nutrients. The study was conducted for 32 d. There were no interaction effects for ADG, average daily feed intake, d-14 respiration rate, or d-14 rectal temperature. Differences in respiration rate and rectal temperature were observed between the HS and TN environments (respiration rate 76 vs 28; rectal temperature, 103.8 vs lO1.8°F). There was an environment x pST interaction for feed efficiency (F/G). The F/G of barrows administered pST was similar in HS (2.23) and TN (2.29) environments. The F/G of placebo-treated barrows increased in HS (3.09) compared to the TN (2.80) environment. These results show that "the growth response of finishing pigs treated with pST is similar in the HS and TN environments.
Keywords: Swine; Heat stress; Energy; Porcine somatotropin; Pig; Growth performance